Spatial relations of the agricultural workforce and rural residents with the uses of agricultural land in the Nashwa sub-district for the year 2011 - Al-Sudani, Manaf Mohammed (Al-Adab Journal, 2015)
Intertwined spatial relationships of phenomena geographic range to enhance our image spatial characteristic of the area without the other and this is what is trying to any study or research to prove it to intensify its way, the analytical relations in this research, which deals with the spatial relationship of the workforce agricultural and rural population uses of agricultural land, as represented by the variables of this research on Maps units cadastral equal values ​​(Chorpleth Maps) after it has been classified data in ways that amount took the nature of these data, this has enabled us trying to figure out the spatial relationship using her technique correlation and technical factor analysis, technical basic components (Principle Compenants) that revealed relationships are built components to arrive at the conclusions of the research.